2016
DOI: 10.1051/0004-6361/201527924
|View full text |Cite
|
Sign up to set email alerts
|

A disk asymmetry in motion around the B[e] star MWC158

Abstract: Context. MWC158 is a star with the B[e] phenomenon that shows strong spectrophotometric variability (in lines and in UV and visible continuum) attributed to phases of shell ejection. The evolutionary stage of this star was never clearly determined. Previous interferometric, spectropolarimetric and spectro-interferometric studies suggest a disk morphology for its environment. Aims. We investigate the origin of the variability within the inner astronomical unit of the central star using near-infrared interferome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 39 publications
4
53
1
1
Order By: Relevance
“…One notable exception is MWC 158 (at graph coordinates (0.85, 0)); this object has been observed with PIONIER before and during the Herbig Large Program, over a time span of ≈2 years, and has been shown (Kluska et al 2016) to have a variable structure on ≈ 2 mas scale, possibly corresponding to the orbital motion of a bright condensation around the central star.…”
Section: Is the Azimuthal Modulation Aligned As We Expect?mentioning
confidence: 99%
“…One notable exception is MWC 158 (at graph coordinates (0.85, 0)); this object has been observed with PIONIER before and during the Herbig Large Program, over a time span of ≈2 years, and has been shown (Kluska et al 2016) to have a variable structure on ≈ 2 mas scale, possibly corresponding to the orbital motion of a bright condensation around the central star.…”
Section: Is the Azimuthal Modulation Aligned As We Expect?mentioning
confidence: 99%
“…However, the image also reveals spiral features that seem to extend from the major axis of the disk. To assess the significance of the features seen in the image we used the bootstrap method, where we reconstructed images from 500 new data sets built by drawing baselines and triangles from the full data set (see Kluska et al 2016). Figure 11 shows the average image computed for all the bootstrap reconstructions together with contours corresponding to the pixel significance levels.…”
mentioning
confidence: 99%
“…There are several clearing mechanisms proposed, like grain growth, photoevaporation, and dynamical clearing by a (sub-)stellar companion (Espaillat et al 2014). Kluska et al (2016) reported a moving asymmetry in the disc of HD 50138, which could be fitted with a circular trajectory with a radius of ∼2 au. However, they could not directly link the asymmetry to the presence of a companion, rather they hypothesized that it may be a spiral arm or other disc asymmetry.…”
Section: Geometric Modellingmentioning
confidence: 97%
“…Following previous near-IR interferometric studies that observed disc asymmetries (e.g., Kluska et al 2016;Koutoulaki et al 2018), we examined the MIDI data to find indications for binarity. The binary signal in the spectrally resolved correlated spectra and differential phases usually appears as a sinusoidal modulation.…”
Section: Binaritymentioning
confidence: 99%